2009
DOI: 10.1097/pai.0b013e31819bfd59
|View full text |Cite
|
Sign up to set email alerts
|

Large Cell Carcinoma of the Lung

Abstract: This study aims to evaluate large cell carcinomas (LCC) of the lung with a panel of immunohistochemical markers in an attempt to identify tumors belonging to other categories. We analyzed a tissue microarray platform of 101 LCC with a panel of 31 monoclonal antibodies. The tumors were 82 (81.3%) classic LCC, 7 (6.9%) neuroendocrine LCC, 6 (5.9%) lymphoepithelioma-like LCC, 3 (2.9%) basaloid LCC, 2 (2%) clear cell LCC, and 1 (1%) LCC with rhabdoid phenotype. Characteristic classic LCC immunophenotype was loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…7 Several recent studies showed that immunostains (and previously electron microscopy 42 ) can reveal the line of differentiation as adenocarcinoma vs squamous cell carcinoma in the majority of large cell carcinomas. 26,36,43,44 The proposed TTF-1/p63 algorithm could be used to determine biological identity within the large cell carcinoma, but this needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several recent studies showed that immunostains (and previously electron microscopy 42 ) can reveal the line of differentiation as adenocarcinoma vs squamous cell carcinoma in the majority of large cell carcinomas. 26,36,43,44 The proposed TTF-1/p63 algorithm could be used to determine biological identity within the large cell carcinoma, but this needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…21 With additional immunostaining using common SCC and ADC IHC markers, about 34% and 25% of LCCs can be further subclassified as ADC and SCC, respectively. 41,42 In a small-sample setting, IHC analysis for p40, p63, CK5/6, CK5, desmocollin 3, TTF1, or napsin A is used as a predictive tool when the tumor shows no morphologic evidence of differentiation (NSCLCnot otherwise specified); predictive accuracy is around 80% to 85% in most unselected studies. 3,6,7,[11][12][13][14][15][16] A subset of cases may even focally express neuroendocrine markers, including chromogranin (9%) and synaptophysin (15%).…”
Section: Cdx2mentioning
confidence: 99%
“…Lymphoepithelioma-like carcinoma (LELC) is one of the rare histological types of lung cancer, classified into one subtype of large cell carcinoma (LCC) (1), with the incidence of 1.15% to 5.90% of total LCC (2,3). It was reported that LELC was commonly found in the relatively young non-smoking Asian population, without a distinctive difference with respect to gender; more than half the patients were at an early stage (stage I and II) and were treated by complete resection (4).…”
Section: Introductionmentioning
confidence: 99%